YouTube Tutorials as Moderator on Technology-Mediated Teaching Approach and Learners’ Inquisitiveness - Medrano, Charity; Melchor, Marciano B. (Journal of Social Work and Science Education, 2024)
The current study delves to evaluate whether YouTube Tutorials have significant moderating effect on the interaction between technology-mediated teaching approach and learners’ inquisitiveness. In this study, the researcher selected the 335 public elementary school teachers in New Corella District, Davao del Norte as the respondents of the study. Non-experimental quantitative research design using descriptive-correlational method was employed. The data collected were subjected on the following statistical tools: Mean, Partial Corelation, and Regression Analysis. Descriptive analysis showed that technology-mediated teaching approach and YouTube Tutorials were described as extensive, while, learners’ inquisitveness was rated as moderately extensive. Further, correlation analysis demonstrated that there is significant relationship technology-mediated teaching approach and learners’ inquisitiveness in New Corella District, Davao del Norte when moderated by YouTube Tutorials. Evidently, regression analysis proved that YouTube Tutorials have significant moderating effect on the interaction between technology-mediated teaching approach and learners’ inquisitiveness in New Corella District, Davao del Norte.